2018
DOI: 10.1007/s12576-018-0627-3
|View full text |Cite
|
Sign up to set email alerts
|

Mst1 promotes cardiac ischemia–reperfusion injury by inhibiting the ERK-CREB pathway and repressing FUNDC1-mediated mitophagy

Abstract: Cardiac ischemia-reperfusion (I/R) injury results mainly from mitochondrial dysfunction and cardiomyocyte death. Mitophagy sustains mitochondrial function and exerts a pro-survival effect on the reperfused heart tissue. Mammalian STE20-like kinase 1 (Mst1) regulates chronic cardiac metabolic damage and autophagic activity, but its role in acute cardiac I/R injury, especially its effect on mitophagy, is unknown. The aim of this study is to explore whether Mst1 is involved in reperfusion-mediated cardiomyocyte d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 58 publications
5
75
0
Order By: Relevance
“…Zhang et al reported that FUNDC1-mediated mitochondria protected heart from I/R injury through maintaining the mitochondrial homeostasis (28). In a recent study, Yu et al found through inhibition of FUNDC1-mediated mitophagy, MST1 could facilitate the cardiac I/R injury (29). In the present study, we also observed obvious inhibition of mitophagy during the I/R or H/R process.…”
Section: Discussionsupporting
confidence: 74%
“…Zhang et al reported that FUNDC1-mediated mitochondria protected heart from I/R injury through maintaining the mitochondrial homeostasis (28). In a recent study, Yu et al found through inhibition of FUNDC1-mediated mitophagy, MST1 could facilitate the cardiac I/R injury (29). In the present study, we also observed obvious inhibition of mitophagy during the I/R or H/R process.…”
Section: Discussionsupporting
confidence: 74%
“…Mst1 promoted cardiomyocyte apoptosis via suppressing autophagy below the physiological levels under oxidative stress [30]. Given its regulating role for apoptosis and autophagy, Mst1 may be a new therapeutic target for preventing cardiomyocyte death [10,23]. In this study, Mst1 inhibition attenuated autophagy suppression, whereas autophagy inhibition by 3-MA application blocked the protective effects of Mst1 inhibition.…”
Section: Discussionmentioning
confidence: 58%
“…I/R injury potentially increases BNIP3 phosphorylation at S17, enhance the binding affinity of LC3, and elevate mitophagy. During I/R, phosphorylation at Y18 and S13 are increased, LC3 affinity decreased with a reduction in mitophagy [97][98][99].…”
Section: Ischemic Heart Diseasementioning
confidence: 99%